Painting outside the lines : patterns of creativity in modern art - Galenson, David W. (Harvard University Press, 2001)
Why have some great modern artists--including Picasso--produced their most important work early in their careers while others--like Cezanne--have done theirs late in life? In a work that brings new insights, and new dimensions, to the history of modern art, David Galenson examines the careers of more than 100 modern painters to disclose a fascinating relationship between age and artistic creativity. Galenson's analysis of the careers of figures such as Monet, Seurat, Matisse, Pollock, and Jasper Johns reveals two very different methods by which artists have made innovations, each associated with a very different pattern of discovery over the life cycle. Experimental innovators, like Cezanne, work by trial and error, and arrive at their most important contributions gradually. In contrast, Picasso and other conceptual innovators make sudden breakthroughs by formulating new ideas. Consequently, experimental innovators usually make their discoveries late in their lives, whereas conceptual innovators typically peak at an early age. A novel contribution to the history of modern art, both in method and in substance, Painting outside the Lines offers an enlightening glimpse into the relationship between the working methods and the life cycles of modern artists. The book's explicit use of simple but powerful quantitative techniques allows for systematic generalization about large numbers of artists--and illuminates significant but little understood features of the history of modern art. Pointing to a new and richer understanding of that history, from Impressionism to Abstract Expressionism and beyond, Galenson's work also has broad implications for future attempts to understand the nature of human creativity in general.